A rapid review investigating the potential impact of a pandemic on the mental health of young people aged 12–25 years. (11th September 2021) - O'Reilly, A.; Tibbs, M.; Booth, A.; Doyle, E.; McKeague, B.; Moore, J.
Abstract: Objectives: In March 2020, the World Health Organization (WHO) officially declared the spread of coronavirus disease 2019 (COVID-19) as a pandemic. Adolescence and early adulthood are peak times for the onset of mental health difficulties. Exposure to a pandemic during this vulnerable developmental period places young people at significant risk of negative psychological experiences. The objective of this research was to summarise existing evidence on the potential impact of a pandemic on the mental health of 12–25 year olds. Methods: A rapid review of the published peer-reviewed literature, published between 1985 and 2020, using PsycINFO (Proquest) and Medline (Proquest) was conducted. Narrative synthesis was used across studies to identify key themes and concepts. Results: This review found 3, 359 papers, which was reduced to 12 papers for data extraction. Results regarding the prevalence of psychological difficulties in youth were mixed, with some studies finding this group experience heightened distress during an infectious disease outbreak, and others finding no age differences or higher distress among adults. Gender, coping, self-reported physical health and adoption of precautionary measures appear to play a role in moderating the psychological impact of an infectious disease outbreak. Most studies were conducted after the peak of an epidemic/pandemic or in the recovery period. Conclusions: More longitudinal research with young people, particularly adolescents in the general population, before and during the early stages of an infectious disease outbreak is needed to obtain a clear understanding of how best to support young people during these events.